An efficient method to evaluate and enhance sport judges' performance during competition: A case study in acrobatic gymnastics - Leon-Prados, J.; Ramos, C. (Science of Gymnastics Journal, 2024)
Who judges the gymnastics judges? How do we measure their accuracy and concordance? How do we know if the judging process is fair? The superior jury has this responsibility. However, they normally lack time to provide effective feedback during competitions.